2020
DOI: 10.1038/s41598-020-78170-z
|View full text |Cite
|
Sign up to set email alerts
|

Geological methane emissions and wildfire risk in the degraded permafrost area of the Xiao Xing’an Mountains, China

Abstract: With global warming, the carbon pool in the degradation zone of permafrost around the Arctic will gradually be disturbed and may enter the atmosphere in the form of released methane gas, becoming an important factor of environmental change in permafrost areas. We selected the northwestern section of the Xiao Xing'an Mountains in China as the study area, located in the degradation zone on the southern margin of the permafrost region in Eurasia, and set up multiple study monitoring areas equipped with methane co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 61 publications
1
48
0
Order By: Relevance
“…We found that during every spring in the study area, a large amount of methane gas is released, which mainly comes from the release of geological methane and microbial methane production in permafrost, and the release of this part of greenhouse gas will lead to an increase of air temperature, it will accelerate the degradation of permafrost, will then play a role in promoting global warming, and also lead to geomorphic changes (Shan et al, 2020a;Shan et al, 2020b;Shan et al, 2021).…”
Section: A Commentary Onmentioning
confidence: 90%
See 4 more Smart Citations
“…We found that during every spring in the study area, a large amount of methane gas is released, which mainly comes from the release of geological methane and microbial methane production in permafrost, and the release of this part of greenhouse gas will lead to an increase of air temperature, it will accelerate the degradation of permafrost, will then play a role in promoting global warming, and also lead to geomorphic changes (Shan et al, 2020a;Shan et al, 2020b;Shan et al, 2021).…”
Section: A Commentary Onmentioning
confidence: 90%
“…The soil composition in the study area contains both fine-grained structures such as clay and coarsegrained structures such as gravelly sandstone. After observation, it was found that the frozen soil layer near the study area is gradually degrading (Shan et al, 2020a), which leads to a higher damping ratio of the soil in the study area, resulting in a faster attenuation of traffic load and a smaller spreading distance. In addition, statistics on landslides near K177 + 550 in the study area found that not only do landslides exist in the area close to the highway, but also in areas far away from the road (845.86 m).…”
Section: A Commentary Onmentioning
confidence: 97%
See 3 more Smart Citations